2017
DOI: 10.1016/j.cois.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Image statistics and their processing in insect vision

Abstract: Natural scenes may appear random, but are not only constrained in space and time, but also show strong spatial and temporal correlations. Spatial constraints and correlations can be described by quantifying image statistics, which include intuitive measures such as contrast, color and luminance, but also parameters that need some type of transformation of the image. In this review we will discuss some common tools used to quantify spatial and temporal parameters of naturalistic visual input, and how these tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 69 publications
2
18
1
Order By: Relevance
“…Surprisingly, we found that the slope constant of the photos of the ground over which the hoverflies were flying was strikingly low, with a mean of 0.78 (Fig. 2 c), much lower than what is normally reported for natural scenes (e.g., Tolhurst et al 1992 ; Dyakova and Nordström 2017 ). Close-up photos often have higher slope constants (Graham and Redies 2010 ), but this does not explain our finding as the photos of the ground over which hoverflies were hovering, taken from the same height, had more typical slope constants (mean of 1.06, blue data, Fig.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Surprisingly, we found that the slope constant of the photos of the ground over which the hoverflies were flying was strikingly low, with a mean of 0.78 (Fig. 2 c), much lower than what is normally reported for natural scenes (e.g., Tolhurst et al 1992 ; Dyakova and Nordström 2017 ). Close-up photos often have higher slope constants (Graham and Redies 2010 ), but this does not explain our finding as the photos of the ground over which hoverflies were hovering, taken from the same height, had more typical slope constants (mean of 1.06, blue data, Fig.…”
Section: Discussioncontrasting
confidence: 67%
“…Extracting alpha may be particularly difficult at low frequencies. We extracted alpha between 0.1 and 1 cpd, as this is most consistent with the literature and with the hoverfly optics (for justification, see Dyakova and Nordström 2017 ), thus avoiding the low-frequency part of the spectrum. However, a closer inspection of the amplitude spectra suggests that whereas the slope for the hovering photos remains similar up to about 6 cpd, the slopes for the flying images depend on the part of the spectrum examined (Figs.…”
Section: Discussionmentioning
confidence: 80%
“…For target–background experiments in both Eristalis and Holcocephala , we used an artificially generated naturalistic background pattern with a slope constant (α) of the amplitude spectrum and rms contrast close to those of natural scenes (Dyakova and Nordström, 2017). To generate this background pattern, we used the fact that the spatial statistics of an image can be quantified by constructing a fast Fourier transform and plotting the rotationally averaged amplitude as a function of spatial frequency (Tolhurst et al, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…This relationship allows us to describe a large two-dimensional amplitude spectrum with a single value (alpha) referred to as the slope constant (Dyakova & Nordström, 2017;Field & Brady, 1997), facilitating comparisons between images (Graham & Field, 2007;Pouli, Cunningham, & Reinhard, 2011;Redies, Hasenstein, & Denzler, 2007;Tolhurst et al, 1992;Torralba & Oliva, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, even among images obtained from similar distances, the slope constant may vary: photos of fields, clouds and coasts have higher slope constants, with more signatures in the lower spatial frequencies, whereas photos of mountains or forests have lower slope constants, with more signatures in the higher frequencies (Torralba & Oliva, ). Nevertheless, the slope constants across a range of natural scenes have been found to typically be close to 1–1.2 (Dyakova & Nordström, ; Tolhurst et al., ).…”
Section: Introductionmentioning
confidence: 99%